2021
DOI: 10.1007/s11538-021-00877-5
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Stoichiometry and Biogeochemistry for Astrobiological Applications

Abstract: A central need in the field of astrobiology is generalized perspectives on life that make it possible to differentiate abiotic and biotic chemical systems McKay (2008). A key component of many past and future astrobiological measurements is the elemental ratio of various samples. Classic work on Earth’s oceans has shown that life displays a striking regularity in the ratio of elements as originally characterized by Redfield (Redfield 1958; Geider and La Roche 2002; Eighty years of Redfield 2014). The body of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 69 publications
(241 reference statements)
1
23
0
Order By: Relevance
“…Such general descriptions for lyfe may not be detailed enough to predict specific biomolecules, but they may still predict more general classes of biosignatures—all of which can still be effective for the detection of Earthly life—that can be used to motivate the detection of truly alien lyfe. These agnostic approaches include homochirality, chemical disequilibria e.g., [ 5 , 6 ], elemental distributions [ 7 ], molecular complexity [ 8 ], and planetary complexity [ 9 ].…”
Section: How One Defines or Characterizes Life Is Critical To Logical...mentioning
confidence: 99%
“…Such general descriptions for lyfe may not be detailed enough to predict specific biomolecules, but they may still predict more general classes of biosignatures—all of which can still be effective for the detection of Earthly life—that can be used to motivate the detection of truly alien lyfe. These agnostic approaches include homochirality, chemical disequilibria e.g., [ 5 , 6 ], elemental distributions [ 7 ], molecular complexity [ 8 ], and planetary complexity [ 9 ].…”
Section: How One Defines or Characterizes Life Is Critical To Logical...mentioning
confidence: 99%
“…One the most consistent patterns associated with life on Earth is the Redfield ratio of elements [19, 28, 58]. Originally discovered in particulate organic matter in seawater [58], this ratio describes the abundances of three of life’s essential elements, relating carbon to nitrogen to phosphorus in a ratio of 106:16:1.…”
Section: Introductionmentioning
confidence: 99%
“…We implemented a single-nutrient chemostat model similar to the model presented in [28] (see Methods). Briefly, our model assumes nitrogen to be replete (due to the high reported concentrations [42, 72]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He showed that low order systems of ordinary and partial differential equations can capture the essence of processes such as embryonic development, tumour growth and disease spread. Kempes et al (2021) applies this philosophy to the field of astrobiology. The paper uses a simple ordinary differential equation model coupled with previously established scaling relationships of the main macromolecular components of cells.…”
mentioning
confidence: 99%